Femoral Biomechanic and microtomography from male rats submitted to dietary restricition supplemented with sucrose - Carvalho, Antônio Augusto F. [UNESP]; Biffe, Bruna Gabriele [UNESP]; Nakamune, Ana Cláudia de Melo Stevanato [UNESP]; Louzada, Mario Jefferson Quirino [UNESP] (My University, 2013)
Food restriction reduces body weight and influence bone mass and also is correlated with bone mineral density (BMD). Mechanisms have been proposed for the loss of BMD after body weight reduction, including reduced energy intake. Growing 8 wk-old Wistar male rats were randomly divided into Control and Calorie restriction associated with sucrose 30% (CRS). These animals were subjected to intermittent food restriction during 8 weeks and had free access to tap water and sucrose30% in distilled water. The rats were euthanized at the end of week 8, blood collected from abdominal aorta artery, femurs cleaned of adherent soft tissues, scanned using dual energy X-ray absorptiometry, structural and material properties determined by three-point bending testing in the mid-diaphyseal region, bone surface tested in a microhardness tester and microstructure was assessed in a microcomputer tomography. In CRS animals body weight decreased significantly relative to the Control animals. There was a clear option for high-sucrose beverage in CRS animals. No difference was observed in biochemical, densitometric and biomechanical analyzes. Results from micro CT showed only significant difference in connectivity of trabecular bone. It has been suggested that rats submitted to food restriction consumed sugar not because of its inherent palatability, but in order to alter their macronutrient balance and animals need to meet energy demands in high-sucrose.
Keywords: Bone mineral density; Femoral biomechanics; Femoral microtomography; Food restriction